The relationship of job satisfaction, burnout, organizational commitment and turnover intention: a study at MAHB corporate office - Revati, Maniraja (2020)
The main objective of this study is to analyse the relationship between job satisfaction, burnout and organizational commitment towards turnover intention among employees of Malaysian Airports Holding Berhad (MAHB). Survey was done through distributing a questionnaire to 270 MAHB employees to participate in the study and was analysed by using Statistics Package for Social Science or SPSS in order to fulfill the objectives of the study. The results showed that there is a significant relationship between the variables towards turnover intention. The factors influencing turnover intention become the main attention from the employer as it is the most important key to ensure the organization well-managed and organized. Thus, internal issues and conflicts need to be clarified to ensure the organizational free from any controversy and leads to be categorized as establish and powerful party. Recommendations have been given which include that the number of sample can be increased to evaluate the relationship in this case study and can be extended towards the workers from different departments and positions who work in private sector organization to compare their relationship between job satisfaction, burnout and organizational commitment on turnover intention. In conclusion, the researcher hopes that more research will be conducted on turnover intention in the future which important to enhance the productivity and satisfaction among workers.